African participation in global agricultural trade - Bouët, Antoine; Sall, Leysa M. (AKADEMIYA2063, 2021)
Combining analyses at the aggregate and sectoral levels offers the richest perspective for understanding Africa’s place in global agricultural trade. International economic theory tells us that the intensity of trade depends on both macroeconomic factors (e.g., factor endowments, exchange rates) and sectoral factors (e.g., factor intensity by sector, access to specific technologies). In the same vein, the notion of “competitiveness” can be applied to a particular product, or to an entire economy.1 Thus, in this chapter, we look at African participation in global agricultural trade both at an aggregated level and at the sectoral level, for eight importantsectors: animals, plants, coffee, cereals, oilseeds, sugar, cocoa, and tobacco. This disaggregated view can help us identify the most promising sectors.